2019
DOI: 10.1016/j.stemcr.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Conversion of Human Fetal Astrocytes into Neurons through Modulation of Multiple Signaling Pathways

Abstract: SummaryWe have previously developed a cocktail of nine small molecules to convert human fetal astrocytes into neurons, but a nine-molecule recipe is difficult for clinical applications. Here, we identify a chemical formula with only three to four small molecules for astrocyte-to-neuron conversion. We demonstrate that modulation of three to four signaling pathways among Notch, glycogen synthase kinase 3, transforming growth factor β, and bone morphogenetic protein pathways is sufficient to change an astrocyte i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(109 citation statements)
references
References 40 publications
4
103
2
Order By: Relevance
“…Besides NeuroD1, other groups have reported that expression of transcription factors Ngn2, Ascl1, Sox2, or combinations of factors can also convert internal glial cells into neurons in the brain or spinal cord (Gascon et al, 2016; Grande et al, 2013; Jorstad et al, 2017; Liu et al, 2015; Niu et al, 2015; Niu et al, 2013; Pereira et al, 2017; Rivetti di Val Cervo et al, 2017; Su et al, 2014). In addition to the overexpression of transcription factors, we have also demonstrated that small molecules can directly convert human glial cells into functional neurons (Yin et al, 2019; Zhang et al, 2015) through transcriptome-wide activation of neuronal genes (Ma et al, 2019). Other groups also reported direct chemical reprogramming of glial cells (Gao et al, 2017) or fibroblast cells (Ambasudhan et al, 2011; Hu et al, 2015; Li et al, 2015) into neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Besides NeuroD1, other groups have reported that expression of transcription factors Ngn2, Ascl1, Sox2, or combinations of factors can also convert internal glial cells into neurons in the brain or spinal cord (Gascon et al, 2016; Grande et al, 2013; Jorstad et al, 2017; Liu et al, 2015; Niu et al, 2015; Niu et al, 2013; Pereira et al, 2017; Rivetti di Val Cervo et al, 2017; Su et al, 2014). In addition to the overexpression of transcription factors, we have also demonstrated that small molecules can directly convert human glial cells into functional neurons (Yin et al, 2019; Zhang et al, 2015) through transcriptome-wide activation of neuronal genes (Ma et al, 2019). Other groups also reported direct chemical reprogramming of glial cells (Gao et al, 2017) or fibroblast cells (Ambasudhan et al, 2011; Hu et al, 2015; Li et al, 2015) into neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the use of diverse small molecule cocktails to reprogram astrocytes into neuronal cells has achieved considerable success [13,14]. Yin et al proved that using three to four small molecules (SB431542, CHIR99021, LDN193189, and DAPT) or their respective functional analogues to modulate the TGF-β/SMAD, BMP, NOTCH, and WNT pathways was su cient to reprogram human foetal astrocytes into neurons [14]. However, RA characteristics are also regulated by other signals, such as the JAK/STAT and P38 MAPK pathways and post-transcriptional levels of several non-coding RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the biological effects of small molecules are netuneable and reversible; thus, their development into pharmaceuticals can provide broad application prospects for neuronal reprogramming without genetic modi cation [12]. The small molecule cocktail of VPA, CHIR99021, RepSox, forskolin, i-BET151, and ISX-9 reprogrammed adult astrocytes into mainly glutamatergic neurons [13], and foetal astrocyte-derived functional neurons could be obtained via mediation by a small molecule cocktail of SB431542, LDN193189, CHIR99021, and 2,4-diamino-5phenylthiazole (DAPT) [14]. However, since the signals activated or inhibited by each small molecule differ, inconsistent chemical combinations lead to variable neuronal properties and conversion e ciencies.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, electrophysiological analysis has proven valuable to define functional neurons, as neurons have very specific electrophysiological features like hyperpolarized membrane potential and spontaneous and triggered action potentials [32,46,49]. In this regard, iNs have been shown to express neuronal markers, show mature neuronal morphology, and possess both spontaneous and induced postsynaptic currents [15,57,81,118,119]. In this regard, iNs have been shown to express neuronal markers, show mature neuronal morphology, and possess both spontaneous and induced postsynaptic currents [15,57,81,118,119].…”
Section: You Are What You Eat: Metabolic Hallmarks Of In Conversionmentioning
confidence: 99%
“…For many studies that are not neuronal function-centered, Ca 2+ imaging and multielectrode arrays can be used as surrogates for electrophysiology and can further deliver insights into neuronal network activity in vitro [20,21,119,120]. In this regard, iNs have been shown to express neuronal markers, show mature neuronal morphology, and possess both spontaneous and induced postsynaptic currents [15,57,81,118,119]. Differentiating neurons in the developing brain and in iPSC differentiation pass through stages that specifically allow them to participate in functional circuits [121], while iNs skip these stages.…”
Section: Updating Our Criteria To Define Neuronsmentioning
confidence: 99%